2007
DOI: 10.1002/elps.200700343
|View full text |Cite
|
Sign up to set email alerts
|

Reliable electrophoretic mobilities free from Joule heating effects using CE

Abstract: Ionic electrophoretic mobilities determined by means of CE experiments are sometimes different when compared to generally accepted values based on limiting ionic conductance measurements. While the effect of ionic strength on electrophoretic mobility has been long understood, the increase in the mobility that results from Joule heating (the resistive heating that occurs when a current passes through an electrolyte) has been largely overlooked. In this work, a simple method for obtaining reliable and reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
(8 reference statements)
0
32
0
1
Order By: Relevance
“…Thus, an approach to obtain more reliable results is to use two detectors along the capillary and substitute the migration time by the difference of times between the second and the first detectors (Dt) and the distance L D by the distance between them (DL D ). The limiting values of mobilities were obtained as suggested by Evenhuis et al [29]. Taking into account that the pK a values of MACs are considerably below 7, we can conclude that they are essentially monocharged anions in the experiments.…”
Section: Mobility Diffusion Coefficient and Hydrodynamic Radiusmentioning
confidence: 99%
“…Thus, an approach to obtain more reliable results is to use two detectors along the capillary and substitute the migration time by the difference of times between the second and the first detectors (Dt) and the distance L D by the distance between them (DL D ). The limiting values of mobilities were obtained as suggested by Evenhuis et al [29]. Taking into account that the pK a values of MACs are considerably below 7, we can conclude that they are essentially monocharged anions in the experiments.…”
Section: Mobility Diffusion Coefficient and Hydrodynamic Radiusmentioning
confidence: 99%
“…It should be noted that the m ep determined from Eq. (37) Evenhuis et al [37] suggest that the variation of m ep with temperature cannot be understood by considering viscosity alone. They found that m ep increased linearly with temperature but the size of the increase depended on the species involved.…”
Section: Use Of L Ep As a Temperature Probementioning
confidence: 98%
“…For temperature increases of up to 201C, m ep increases linearly with temperature [37], making it suitable for use as a temperature probe [13].…”
Section: Variation In Physical Properties Of Materials With Temperaturementioning
confidence: 99%
See 2 more Smart Citations